Heart rate variability in patients with tetralogy of Fallot. (14th October 2021) - Otero Luna, A V; Church, S; Loza, A; Rueda-Ochoa, O L; Rey Coy, M A; Gonzalez Marin, C H; Beach, C
Abstract: Background: Heart rate variability (HRV) can be used to evaluate cardiac autonomic nervous system activity. In the adult population decreased HRV has been associated with increased mortality in patients with cardiac disease, however, application of HRV in patients with congenital heart disease is not well established. Purpose: To describe and compare HRV parameters obtained by clinical Holter monitoring in patients with Tetralogy of Fallot (TOF) and healthy controls and to evaluate its association with different clinical outcomes. Methods: Data from 489 patients were obtained; 150 had undergone repair of TOF and 339 were healthy controls. Using propensity score matching (PSM), 149 TOF patients were matched for sex, age at Holter, body mass index, use of beta-blockers, and ectopic beats with 149 healthy patients. Minimum, maximum, average heart rate and time domain HRV parameters (ASDNN5, SDANN5, SDNN, RMSSD, PNN50) and clinical outcomes (arrhythmias, hospital admission for cardiac disease, and functional class) were compared between groups using simple and multiple linear regression models as well as logistic regression analysis. Results: No significantdifference was found in time domain HRV parameters between the two groups, though average (−7.0253, p=0.000) and maximum (−15.8585, p=0.000) heart rate values were significantly lower in patients with TOF compare with controls. Logistic regression analysis showed an association between maximum heart rate values and the development of arrhythmias (OR=0.9817, p=0.013), as well as the functional class (OR=0.9706, p=0.03). Conclusion: Average and maximum heart rates are significantly lower in patients with repaired TOF compared to the control population. Time domain HRV parameters were not associated with clinical outcomes in patients with TOF when compared to healthy controls. Further investigation assessing frequency domain parameters may provide further insight. Funding Acknowledgement: Type of funding sources: None.